Stock Valuation and Business Performance of PT Indofood Cbp Sukses Makmur Tbk Amidst Wheat Price Volatility During The Russia-Ukraine Crisis - Arbrianto, Dimas; Rahadi, Raden Aswin (Green Publisher Indonesia, 2023)
The Russia-Ukraine Crisis in 2022 adversely affected the business performance of PT Indofood CBP Sukses Makmur Tbk (ICBP), the largest noodle manufacturer in Indonesia, due to volatile wheat prices. During Q2, ICBP witnessed a 16% growth in net revenue but a substantial 40.1% decline in profit, primarily attributed to escalating commodity prices. This negative trend persisted in Q3, resulting in a significant 33.4% decrease in net profit despite increased sales. Consequently, ICBP’s stock price experienced a decline. In this context, conducting a comprehensive fundamental analysis that integrates various macroeconomic factors is crucial to evaluate the company’s valuation. This study aims to determine the valuation of the ICBP amidst wheat price volatility during the Russia-Ukraine crisis. This study employs multiple analysis approaches, including financial ratio analysis, intrinsic valuation using free cash flow to firm (FCFF), and relative valuation analysis employing price-earnings ratio (P/E) and enterprise value to EBITDA (EV/EBITDA) ratios. The intrinsic valuation of ICBP suggests a fair stock value of 13,806 Rupiah per share, while the current share price is 10,000 Rupiah per share, indicating an undervaluation of approximately 27.6%. Similarly, the relative valuation analysis reveals that ICBP is undervalued compared to industry peers based on P/E and EV/EBITDA ratios. These findings indicate that ICBP is presently undervalued, presenting an opportunity for future appreciation of its share price.